VD_FINDINFO Décision / 2011 / 710 vom 25. November 2011 - VD Tribunal cantonal (2011)
COMPÉTENCE RATIONE LOCI, JONCTION DE CAUSES, DÉCISION D'IRRECEVABILITÉ | 38 CPP (CH), 39 CPP (CH), 40 CPP (CH), 41 CPP (CH)